About bibliographical projects during the formation of the mathematical community in Europe: Portuguese mathematicians in international bibliography at the turn of the XIX-XX centuries - Kharlamova, Vera I. (2022)
We consider the possibility of using bibliographic as well as reference data for research in the history of mathematics during the formation of the mathematical scientific community in Europe at the second half of the XIX-the first half of the XX centuries. Considering an example of the mathematical scientific community in Portugal, which was still being formed at that time, we explore participation and citing of Portuguese researchers in different bibliographic European projects. We note that bibliographic data can be interpreted in the broader context of the history of Europe as a whole: the link between this local process in the history of mathematical thought and the European historical process can be easily seen in the changing number of publications produced by the mathematical scientific community in Portugal over different time periods. We conclude that the evolution dynamics of international bibliography of the mathematical scientific communities in different countries can be used as a research methodology to understand the social history of mathematics.